PHYTOCHEMISTRY STUDY OF PLANTS BELONGING TO CAPPARIS - Al-Mahweety, Jamal A.N.; Alyahawi, Ali (Universal Journal of Pharmaceutical Research, 2020)
Objectives: Bioactive molecules have gained attention in recent time due to their diverse effects and their economic importance. The objective of current study was to isolate, analyze and identify the active constituents from leaves of C. cartilaginea. Methods: The powdered leaves were extracted with different solvents by using Soxhlet apparatus and carried out by different chromatographic techniques. The phytochemical characterizations were evaluated by nuclear magnetic resonance and mass spectrometry. Results: Three pure compounds were identified representing 1.6% of the total phytochemical composition. Yield of compounds 1, is Kaempferol (6gm), compound 2, is Dihydroxy-lup-20(29)-en-28-oic acid (3.8gm) and compound 3, is β-Sitosterol (5gm). Three of them are report for first time from this Spp. Conclusion: From this study, can be concluded that report for the first time from C. cartilaginea leaves, identified 3 pure chemical compounds, by analysis using various physical and spectral techniques. Peer Review History: Received 4 February 2020; Revised 11 March; Accepted 23 April; Available online 15 May 2020 Academic Editor: Dr. DANIYAN Oluwatoyin Michael , Obafemi Awolowo University, ILE-IFE, Nigeria, toyinpharm@gmail.com Reviewer(s) detail: Ahmad Najib , Universitas Muslim Indonesia, Makassar, Indonesia, ahmad.najib@umi.ac.id Prof. Dr. Ali Gamal Ahmed Al-kaf , Sana'a university, Yemen, alialkaf21@gmail.com